Wawasan Fikih Indonesia: Studi tentang Periwayatan dan Penalaran Hukum Wali Nikah - Lahaji Lahaji; Sulaiman Ibrahim (Al-Ulum, 2019)
This study reinforces the issue of guardian marriage referred to in the law number 26, which returned to the article 2 that emphasizes that the provisions of religious law are the primary determinant of the validity of a marriage. Because in principle, a woman has no right to marry herself, so women marry other women. Indonesian jurisprudence about marriage guardian law is contained in the Law and the KHI. In Law Number 1 of 1974, it is unclear how to regulate marriage guardians, but it is required that there be a parent's permission for those who are married if they are not yet 21 years old. In the practice of the Religious Courts, the guardian of marriage is a necessity for the marriage to be valid, even the guardian of the marriage must also be assessed whether the mujbir guardian or the regular guardian.